DIPLOMASI BUDAYA INDONESIA MELALUI PROGRAM BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) DI TURKI - Salman, Amar Nur; ', Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Cultural diplomacy is an important instrument in strengthening relations between countries through a cultural approach. Indonesia, as a country with rich culture, utilizes the Indonesian Language for Foreign Speakers (BIPA) program as a cultural diplomacy effort. The BIPA program in Turkey is a clear example of how Indonesia introduces its language and culture on the international stage, while strengthening bilateral relations with Turkey. Through this program, Indonesia not only introduces language, but also cultural values and national identity to foreign communities. This research aims to find out how Indonesian cultural diplomacy works through the Indonesian language program for foreign language speakers in Turkey. The research method used is qualitative with data collection techniques in the form of literature study. The approach used in this research is a cultural diplomacy theory with a country level of analysis is used to explain how countries as the main actors in cultural diplomacy play a role in strengthening relations between countries through culture. The research results show that the BIPA program in Turkey is included in Indonesia's cultural diplomacy activities. This program includes forms of cultural activities, the actors involved, as well as the goals to be achieved, namely creating a positive image of Indonesia through language teaching and spreading culture. Through this program, Indonesia has succeeded in building a deeper understanding and appreciation of Indonesian culture among Turkish society as evidenced by the number of participants, positive responses, and survey results that show a positive image of Indonesia in Turkey. Keywords: Cultural Diplomacy, BIPA, Indonesia, Turkey